Malaysia's Economic Growth and Transition to High Income : An Application of the World Bank Long Term Growth Model - Devadas, Sharmila; Guzman, Jorge; Kim, Young Eun; Loayza, Norman; Pennings, Steven (World Bank, Washington, DC, 2020)
This paper studies economic growth in Malaysia, with the purpose of assessing the potential to attain the status and characteristics of a high-income country. Future economic growth is simulated under a business-as-usual baseline, where the growth drivers follow their historical or recent trends, and under different scenarios of reform, using the World Bank Long-Term Growth Model (LTGM). Under the business-as-usual baseline, Malaysia's GDP growth is expected to decline from 4.5 to 2.0 percent over the next three decades, following the country's transition to high income in 2024 (which might be delayed due to the effects of COVID-19). This decline is partly due to demographics, but also a declining marginal product of private capital and slowing growth rates of total factor productivity and human capital. Strong reforms are required for Malaysia to grow beyond what is expected based on historical trends, especially for human capital, female labor force participation, and total factor productivity. In the strong reform scenario, based on growth drivers achieving a target corresponding to the 75th percentile of high-income countries, GDP growth is expected to have a substantially higher trajectory, reaching 3.6 percent by 2050.